Dentists' attitude to provision of care for people with learning disabilities in Udaipur, India - Nagarajappa, Ramesh; Tak, Mridula; Sharda, Archana J.; Asawa, Kailash; Jalihal, Sagar; Kakatkar, Gauri (Scandinavian journal of caring sciences, 2013)
Scand J Caring Sci; 2013; 27; 57–62 Dentists’ attitude to provision of care for people with learning disabilities in Udaipur, India This study determines and compares the attitudes of dentists to the provision of care for people with learning disabilities according to gender, qualification, previous experience of treating patients with learning disabilities and work experience of dentists. A cross‐sectional study was conducted among 247 dentists (166 men and 81 women) using a pretested structured questionnaire. This questionnaire assessed the respondent’s attitude towards learning‐disabled patients in five categories: beliefs about treating them, their capabilities, discrimination against these patients, their social behaviour and quality of care to be received by these patients. The information on dentist’s gender, qualification, work experience and previous experience of treating patients with learning disabilities was also collected through questionnaire. The Student’s t‐test and anova test were used for statistical analysis. The mean attitude score was found to be 71.13 ± 8.97. A statistically significant difference was found in the mean attitude scores of dentists with work experience (p = 0.000). Study subjects with postgraduate qualification and previous experience of treating patients with learning disabilities had significantly greater mean attitude score than their counterparts (p = 0.000). The overall attitude of dentists towards provision of care for people with learning disabilities was favourable, which increased with higher qualification and past experience.